Interpersonal Trust Relationship With College Students' Marriage Readiness - Annisa Fitria Suherman; Rina Nurhudi Ramdhani (Ma'soem University, 2024)
This study aims to investigate the description of interpersonal trust and marriage readiness in college students. The method used in this research is a case study with questionnaire and interview techniques to obtain in-depth understanding. This research seeks to answer the research question, namely how the level of interpersonal trust influences marriage readiness in students. The aim is to understand the relationship between interpersonal trust in shaping marriage readiness among students. Apart from that, it also serves as a guide in developing guidance and counseling programs to increase marriage readiness among students. The results of the analysis show that the average student has a high level of interpersonal trust and marriage readiness.